Continuity or change in the transition to Islam? A diachronic assessment of agricultural production at Old Dongola, Northern Sudan (14th–18th centuries CE) - Mohammed Nasreldein; Simone Riehl; Artur Obłuski (PLoS ONE, 2026)
In this paper, we present an archaeobotanical study from Old Dongola, northern Sudan, examining agricultural dynamics and subsistence strategies from the Late Christian to the Islamic period. Old Dongola, established in the 5th century, served as the capital of the Kingdom of Makuria, one of the three medieval Nubian kingdoms. Following the collapse of Makuria in the 14 th century, the city underwent significant cultural and social transformations, marked by the migration of Arab tribes and the rise of new power structures. From the 14 th to the 18 th century, Old Dongola served as the seat of a local ruler who became subordinate to the Funj Sultanate in the 16 th century, a period that witnessed religious conversion, migration, and political reorganisation associated with the gradual conversion to Islam in the region. This study is distinguished by a systematic sampling strategy, with sediments collected from every excavated context in the citadel of Old Dongola. The archaeobotanical results, spanning the Kingdom of Dongola and Funj periods (14 th –18 th centuries), shed light on the dietary habits of the site's inhabitants. The evidence indicates an increasing reliance on sorghum, alongside a gradual decline of bread wheat and hulled barley. The introduction of crops such as tobacco and eggplant from the 16 th century onwards may reflect broader economic and cultural shifts occurring during this period of religious and demographic change, though a direct causal link between these crop introductions and processes of demographic change or conversion to Islam cannot be established from archaeobotanical evidence alone. This study contributes to our understanding of agricultural change in early modern Sudan, adding to an understudied archaeobotanical record at a time of significant socio-political transition.